Revised Maximum Depositional Age for the Ediacaran Browns Hole Formation: Implications for Western Laurentia Neoproterozoic Stratigraphy - Ashley W. Provow; Dennis L. Newell; Carol M. Dehler; Alexis K. Ault; W. Adolph Yonkee; Stuart N. Thomson; Kevin H. Mahan (Lithosphere, 2021)
AbstractConstraining the depositional age of Neoproterozoic stratigraphy in the North American Cordilleran margin informs global connections of major climatic and tectonic events in deep time. Making these correlations is challenging due to a paucity of existing geochronological data and adequate material for absolute age control in key stratigraphic sequences. The late Ediacaran Browns Hole Formation in the Brigham Group of northern Utah, USA, provides a key chronological benchmark on Neoproterozoic stratigraphy. This unit locally comprises <140 m of volcaniclastic rocks with interbedded mafic-volcanic flows that lie within a 3500 m thick package of strata preserving the Cryogenian, Ediacaran, and the lowermost Cambrian history of this area. Prior efforts to constrain the age of the Browns Hole Formation yielded uncertain and conflicting results. Here, we report new laser-ablation-inductively-coupled-mass-spectrometry U-Pb geochronologic data from detrital apatite grains to refine the maximum depositional age of the volcanic member of the Browns Hole Formation to 613±12 Ma (2σ). Apatite crystals are euhedral and pristine and define a single date population, indicating they are likely proximally sourced. These data place new constraints on the timing and tempo of deposition of underlying and overlying units. Owing to unresolved interpretations for the age of underlying Cryogenian stratigraphy, our new date brackets two potential Brigham Group accumulation rate scenarios for ~1400 m of preserved strata: ~38 mm/kyr over ~37 Myr or ~64 mm/kyr over ~22 Myr. These results suggest that the origins of regional unconformities at the base of the Inkom Formation, previously attributed to either the Marinoan or Gaskiers global glaciation events, should be revisited. Our paired sedimentological and geochronology data inform the timing of rift-related magmatism and sedimentation near the western margin of Laurentia.